Exploring challenges of access to Non-Communicable Disease (NCD) prevention, treatment and care: A qualitative study on people living with NCDs (PLWNCDs) in West Bengal, India - Sutapa Biswas; Debayan Podder; Sweety Suman Jha; Prachi Kathuria; Bobby Paul (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: People living with noncommunicable diseases (PLWNCDs) are often disproportionately affected due to adverse interaction with socioecological and biological factors. Hence, it is imperative to learn from their lived experience to gain a greater understanding of interactions as well as explore their priorities and needs in accessing care and identify areas of priority action through multistakeholder engagement. MATERIALS AND METHODS: The qualitative study with grounded theory approach was conducted between October and December 2020. An online key-informant interview with the health policymaker, virtual group discussion with eight PLWNCDs, and in-depth telephonic interviews with five PLWNCDs were conducted, after obtaining informed consent using interview guide, developed, and validated by the experts. Data collection continued till data saturation was achieved. Transcripts generated from the interview recordings were coded using hand-code technique and analyzed thematically. RESULTS: Challenges faced by PLWNCDs in accessing care were lack of empathy and support from health-care professionals, stigma, financial hardship, and hospital overcrowding. Caregivers emphasized on the felt need to involve civil society organizations (CSOs) in raising awareness toward noncommunicable diseases (NCDs) at family, community, and policymaking levels. The need for home-based NCD care and rehabilitation centers was voiced by the PLWNCDs. Impediments toward effective implementation of NCD policies were adoption of a "top-down" approach, poor awareness about government health insurance schemes, skewed distribution of empanelled hospitals in and around cities, nonavailability of qualified health-care professionals in underserved areas, aggravated allocation-utilization disparity during COVID-19 pandemic, and lack of robust information technology infrastructure to support access to telemedicine services. CONCLUSION: The collective role of governments, CSOs, and health-care providers, along with meaningful involvement of PLWNCDs, would help to create an enabling environment for overcoming the challenges of access to care and thus achieve universal health coverage.